2019
DOI: 10.1002/jcp.28051
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ENT1 increases cell proliferation in the annulus fibrosus of the intervertebral disc

Abstract: Mice lacking equilibrative nucleoside transporter 1 (ENT1 −/−) demonstrate progressive calcification of spinal tissues including the annulus fibrosus (AF) of the intervertebral disc (IVD). We previously established ENT1 as the primary nucleoside transporter in the AF and demonstrated dysregulation of biomineralization pathways. To identify cellular pathways altered by loss of ENT1, we conducted microarray analysis of AF tissue from wild‐type (WT) and ENT1 −/− mice before calcification (2 months of age) and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
(117 reference statements)
0
11
0
Order By: Relevance
“…Since tissues from multiple mice were pooled, we are unable to correlate molecular profiles with individual animal behavior. Pooling tissue is an approach used by other groups to perform parallel analyses on limited starting tissues 52 . As the sensitivity of OMIC analyses improves, studies of tissues from individual animals, or even specific cell-types, should be performed to overcome the limitations of the present work.…”
Section: Discussionmentioning
confidence: 99%
“…Since tissues from multiple mice were pooled, we are unable to correlate molecular profiles with individual animal behavior. Pooling tissue is an approach used by other groups to perform parallel analyses on limited starting tissues 52 . As the sensitivity of OMIC analyses improves, studies of tissues from individual animals, or even specific cell-types, should be performed to overcome the limitations of the present work.…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking ENT1, a model of diffuse idiopathic skeletal hyperostosis, show reduced expression of ANK, ENPP1, and ALPL in discs, increased AF cell proliferation, and progressive ectopic calcification of fibrous connective tissues along the spine (Warraich et al, 2013). Analyses of AF tissue isolated from ENT1 knockout mice has further revealed that the observed increased cell proliferation is associated with an upregulation of E2F transcription factors, the cell cycle regulators RB1 and CDK2, and stimulation of the JNK/MAPK pathway (Veras et al, 2019). Notably, the importance of genetic background in the ectopic calcification process has been recently demonstrated by the study of LG/J inbred mice, which show an agedependent increase in dystrophic mineralisation of discs (this mouse strain will be discussed later in the review) (Novais et al, 2020).…”
Section: Extracellular Matrix and Its Turnovermentioning
confidence: 99%
“…We have explored the effect of mechanical loading on the IVD in mice [42][43][44] and used transgenic mice to study IVD development, 45 disc degeneration, 16,46 and diffuse idiopathic skeletal hyperostosis (DISH). [47][48][49][50] Important insights have likewise been provided by others using mouse models to study disc development, [51][52][53] inflammation, 54 IVD degeneration, 10,13,[55][56][57][58] calcification, 59,60 and scoliosis. [61][62][63] The multitude of available mouse models of spine pathologies allows for global molecular comparisons to uncover novel biological insights.…”
Section: Introductionmentioning
confidence: 99%
“…Proteomics has also been used in mice for global characterization of the healthy IVD, 73 to examine the response to mechanical loading, 42 to characterize different mouse strains, 55 and to investigate ectopic calcification in the IVD. 48 To date, there have been no metabolomic studies of murine IVD tissues, and the analysis of human IVD tissues is limited to a single unbiased metabolite screen using high-resolution magic angle spinning (HR-MAS) nuclear magnetic resonance (NMR), 74 which is much less sensitive than MS based metabolomics. 75 Despite the limitations to the starting quantity of sample associated with the small size of the mouse, it is possible to gain novel insights into mechanisms, biomarkers and therapeutic targets of IVD pathologies using optimized protocols for proteomic and metabolomic analyses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation